Cultura da Convergência - Christofoletti, Rogério (Brazilian journalism research, 2008)
Three ideas would suffice for the reading of “Cultura da Convergência” (Culture of Convergence) by Henry Jenkins to be of interest to journalists and researchers in the area: media convergence as a cultural process; the strengthening of an emotional economy which guides consumers of symbolic goods and media creators; the expansion of trans-media narrative forms.